Tinjauan Empat Mazhab terhadap Penetapan Waktu Ihtiyath pada Jadwal Salat Fardu (Analisis Perbandingan): Review of Four Schools of Determination of Ihtiyath Times in the Fardu Prayer Schedule (Comparative Analysis) - Muhammad Taufan Djafri; Putra Alam; Miftahul Jannah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to determine the views of four schools of thought on the determination of iḥtiyāth time in the obligatory prayer schedule. This study uses a library research type that focuses on collecting data and information with the help of all materials available in the library and outside the library using a normative and comparative approach. The results of the study are as follows; First, the addition of iḥtiyāth time to the obligatory prayer schedule is necessary so that a person can perform prayers on time, also as a form of standardization of prayer times in a city. In addition, iḥtiyāth time is necessary because there are roundings in data collection and simplification of calculation results to the minute unit. Second, astronomers established this iḥtiyāth method based on the hadith about the recitation of 50 verses of the Qur'an between sahur and dawn, also in the hadith prohibiting performing prayers at sunrise, sunset, and istiwâ (culminating above) and the generality of the hadith about leaving doubtful matters. Third, the views of the 4 schools of thought on the time of iḥtiyāth are that they practice and argue with the time of iḥtiyāth in determining prayer times. However, what differentiates the concept of iḥtiyāth in the obligatory prayer schedule is the difference in adding and subtracting prayer times and the factors or causes for determining the time of iḥtiyāth. The polemic regarding determining prayer times is an issue that needs to be studied more deeply because current developments greatly influence various aspects of people's lives, including the implementation of prayer. So we need to refer back and study the correct method in determining prayer times so that we remain within the corridor and direction of religious law.